Pengaruh Due Professional Care, Time Budget Pressure, Etika Auditor Dan Fee AuditorTerhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik Di Surakarta Dan Semarang) - Aisyah, Fitriyatul; , Drs. Agus Endro Suwarno, M.Si (2017)
Purpose of the research was to know effect of due ofessional care, timebudget pressure, auditor's ethics and auditor's fee on quality of audit. Populationof the research was auditors working in Public Accountant Offices of Surakarta and Semarang.Sample was taken by using convenience sampling. Sample of the researchwas 54 respondents. Analysis data of the research used multiple regressionanalysis.Results of the research indicated that coefficient of determination of the multiple regression was adjusted R2 of 0.847. It means that 84.7% of variablevariances consisting of due professional care, time budget pressure, auditor'sethics and auditor's fee and the rest of 15.3% were explained by factors other thaninvestigated in the research. Results of t-testindicated that due professional careand time budget pressure had no significant effect on quality of audit, whereasauditor's ethics and auditor's fee had significant effect on the audit quality.